2015
DOI: 10.1039/c4sm01994f
|View full text |Cite
|
Sign up to set email alerts
|

Influence of imidazolium based green solvents on volume phase transition temperature of crosslinked poly(N-isopropylacrylamide-co-acrylic acid) hydrogel

Abstract: The volume phase transition temperature (VPTT) of crosslinked poly(N-isopropylacrylamide-co-acrylic acid) (PNIPAM-co-AA) hydrogel in water in the presence of five imidazolium based ionic liquids (ILs) was studied. The VPTT of PNIPAM-co-AA hydrogel can be modulated to different extents by the addition of different amounts of ILs. The modulations in VPTT values can be attributed to the IL-induced alterations in hydrophobic, hydrophilic and hydrogen bonding interactions of PNIPAM-co-AA hydrogel with the neighbori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 42 publications
0
17
0
Order By: Relevance
“…Besides, since water molecules have preferential interactions with hydrophilic ILs, the hydration of polymers in aqueous solution may be destabilized 32 Therefore, the introduction of hydrophilic IL additives may weaken the thermo-responsive behavior of polymers and depress the LCST. [32][33][34][35] Since IL monomers are chemically polymerized into polymer networks in the present study, the strong interaction between the PIL moiety and water molecule exactly promotes the swelling behavior of microgels and increases the transition temperature. Considering the influence of the crosslinking extent on the thermal property of LCST-type gels, it is observed that gel systems with higher crosslinking degrees lead to higher LCST with a broader transition process, due to the more constrained environment of molecular motions.…”
Section: Dls Measurementsmentioning
confidence: 92%
See 1 more Smart Citation
“…Besides, since water molecules have preferential interactions with hydrophilic ILs, the hydration of polymers in aqueous solution may be destabilized 32 Therefore, the introduction of hydrophilic IL additives may weaken the thermo-responsive behavior of polymers and depress the LCST. [32][33][34][35] Since IL monomers are chemically polymerized into polymer networks in the present study, the strong interaction between the PIL moiety and water molecule exactly promotes the swelling behavior of microgels and increases the transition temperature. Considering the influence of the crosslinking extent on the thermal property of LCST-type gels, it is observed that gel systems with higher crosslinking degrees lead to higher LCST with a broader transition process, due to the more constrained environment of molecular motions.…”
Section: Dls Measurementsmentioning
confidence: 92%
“…In fact, when IL additives are involved in LCST-type polymer based systems, the temperature induced phase transition behaviors can be altered by the complicated interactions between polymer, ILs and water, which have been investigated in detail. [31][32][33][34][35] However, as far as we know, there are few studies that have focused on the thermal phase behavior of POEGMA based systems involved with IL or PIL, and the impact of PIL moieties as polymerized constituents on the dynamic volume phase transition mechanism of thermo-responsive gel systems has seldom been discussed.…”
Section: Introductionmentioning
confidence: 99%
“…It is well-known that the volume phase transition is determined by the hydrophobic interactions within the PNiPAM molecule. Indeed, many studies have shown that the VPTT is modified by the addition of inorganic salts, 18 surfactants, 16,19 ionic liquids, 20,21 alcohols, 22 and urea. 17,23 Besides that, the VPTT and swelling/deswelling behavior are also modified by the introduction of charged groups (e.g., carboxyl, sulfonic, and amino group) into the PNiPAM microgel network.…”
Section: Introductionmentioning
confidence: 99%
“…Synthetic polymers, particularly stimuli responsive polymers, have received extensive attention and opened a broad field of potential applications in bioimaging, drug delivery, tissue engineering and bioactive surfaces [1,2,3,4,5], due to their extraordinary response to changes in temperature, pH, ionic strength and enzymes [6,7,8,9,10,11,12,13,14]. Among hundreds of polymers, poly( N -isopropylacrylamide) (PNIPAM) and its derivatives have widely been applied in protein science [15,16,17,18].…”
Section: Introductionmentioning
confidence: 99%